Optimization of Welding Process Parameters for 9Cr-1Mo Steel Using RSM and GA. Issue 3 (17th February 2016) - Nagaraju, S.; Vasantharaja, P.; Chandrasekhar, N.; Vasudevan, M.; Jayakumar, T.
Abstract : Optimization of A-TIG welding process parameters for 9Cr-1Mo steel has been carried out using response surface methodology (RSM) and genetic algorithm (GA). RSM has been used to obtain the design matrix for generating data on the influence of process parameters on the response variables. A second-order response surface model was developed for predicting the response for the set of given input variables. Then, numerical and graphical optimization was performed using RSM to obtain the target depth of penetration (DOP) and heat-affected zone (HAZ) width using desirability approach. Multiple regression models were developed based on the generated data, and then the models were used in GA to determine the optimum process parameters for achieving the target DOP and HAZ width. GA-based models employed two different selection processes. Both the RSM- and GA-based models suggested a number of solutions in terms of process parameters, and the identified solutions were validated by experiments. GA-based model employing tournament selection has been found to be a more accurate method for determining the optimum A-TIG welding process parameters.